Studi Tentang Tingkat Kepuasan Jemaat Terhadap Musik Iringan dalam Ibadah di Gereja Kalimantan Evangelis Sinta Asi di Kota Muara Teweh - Edwin Meko Taka Melas; Yuliati Eka Asi (Institut Agama Kristen Negeri Palangka Raya, 2022)
Church Accompaniment Music is an instrument that produces a beautiful and melodious tone and plays one of the important roles in Church Worship. However, it is not yet known the congregation's response to the accompaniment music. This research was conducted to find out and describe the congregation's satisfaction with the music of worship accompaniment. The method used is descriptive quantitative. The sample of this study was the congregation of GKE Sinta Asi Muara Teweh with a sampling quota technique. Data collection techniques using questionnaires and documentation. Data analysis techniques by using data frequency distribution tables and guideline tables to describe data. Of the 31 respondents to the congregation of the Kalimantan Evangelical Church Sinta Asi Muara Teweh stated that they were satisfied with the accompaniment music and it was functioning properly and in accordance with the needs of the congregation to worship. It was shown that 20 respondents (54.50%) stated good, 9 respondents (29.10%) stated quite good. Of the different types of accompaniment used: 71% of respondents stated that worship was more satisfied accompanied by a piano (without a rhythm keyboard). There were 22.60% of respondents who stated that worship could be accompanied by other musical instruments. Based on the aspect of the congregation living or not: there are 61.35% of respondents living and 32.35% of respondents feeling less passionate. Musik Iringan Gereja merupakan suatu suatu instrumen yang menghasilkan suatu nada yang indah dan merdu serta memainkan salah satu peranan penting dalam Ibadah Gereja. Namun belum diketahui tanggapan jemaat terhadap musik iringan. Penelitian ini di lakukan untuk mengetahui dan mendeskripsikan kepuasan jemaat terhadap musik iringan ibadah. Metode yang digunakan adalah deskriptif kuantitatif. Sampel penelitian ini adalah jemaat GKE Sinta Asi Muara Teweh dengan teknik kuota sampling. Teknik pengumpulan data menggunakan kuesioner dan dokumentasi. Teknik analisis data dengan menggunakan tabel distribusi frekuensi data dan tabel pedoman untuk mendeskripsikan data. Dari 31 orang responden jemaat Gereja Kalimantan Evangelis Sinta Asi Muara Teweh menyatakan sudah merasa puas terhadap musik iringan dan sudah berfungsi dengan baik dan sesuai dengan kebutuhan jemaat untuk beribadah. Hal ini ditunjukan bahwa 20 responden (54,50%) menyatakan baik, 9 responden (29,10%) menyatakan cukup baik. Dari perbedaan jenis iringan yang digunakan: 71% responden menyatakan ibadah lebih puas diiringi dengan piano (tanpa rhythm keyboard). Terdapat 22,60% responden menyatakan ibadah dapat diiringi alat musik lain. Berdasarkan aspek jemaat menghayati atau tidak: terdapat 61,35% responden menghayati dan 32,35% responden merasa kurang menghayati.